Reasons for encounter and diagnoses at primary care level in Klipfontein subdistrict, Cape Town metropole. - Kumari, J. (Stellenbosch : University of Stellenbosch, 2016)
ENGLISH ABSTRACT: Aim: To enumerate the reasons for encounter (RFE) and the diagnoses (pre-existing or new) of patients seen in Klipfontein sub-district of the Western Cape.